Gamification, Hedonic Motivation, and Perceived Value on Impulse Buying among Generation Z GoFood Users - Afina Salsabila; Tengku Firli Musfar; Sri Wahyuni Wildah (CV. Rayyan Dwi Bharata, 2026)
This study aims to analyze the effect of gamification on impulse buying through hedonic motivation and perceived value among Generation Z GoFood users in Pekanbaru. This issue is important to examine because a pre-survey of 30 Generation Z GoFood users in Pekanbaru showed that most respondents felt encouraged to make unplanned purchases after exposure to reward features and limited-time promotions, yet the underlying psychological mechanism remains underexplored in developing-city contexts. A quantitative approach was used, with data collected from 120 respondents through purposive sampling. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, chosen for its suitability with a moderate sample size and its capacity to test mediating relationships simultaneously. The results show that gamification has a positive and significant effect on impulse buying, hedonic motivation, and perceived value. Hedonic motivation also has a positive and significant effect on impulse buying and successfully mediates the relationship between gamification and impulse buying. However, perceived value does not significantly affect impulse buying and fails to mediate the relationship. These findings indicate that emotional factors play a more important role than cognitive evaluation in driving impulse buying behavior, so future research is recommended to broaden the geographic scope and incorporate other emotional variables such as fear of missing out (FOMO) or customer engagement.